Fibro-osteochondroma of the uterus - Alan W. H. Bates; Manisha Ram (Wolters Kluwer Medknow Publications, 2012)
A case of a uterine fibro-osteochondroma in a 61-year-old woman with postmenopausal bleeding was presented. Ultrasound revealed a calcified lesion in the posterior wall of the uterus and a hysterectomy was performed. Histopathologic examination showed a well-circumscribed triphasic tumor composed of peripheral lobules of mature hyaline cartilage and foci of trabecular bone with a core of loosely arranged fibroblast-like, spindle cells. This is the second reported case of fibro-osteochondroma, which has been described only in the uterus. Diagnosis requires thorough histopathologic examination to exclude metaplasia within a leiomyoma or uterine sarcoma. It is histologically benign and complete excision should be curative.